Análise da influência do cromo trivalente e hexavalente na formação dos compostos de hidratação de pastas de cimento - Savicki, Gabriela (Universidade do Vale do Rio dos Sinos, 2022)
The search for more sustainable treatment technologies for industrial waste to avoid their final disposal in landfills is growing, especially for hazardous waste. Chromium (Cr) is a metal that can bring the characteristic of toxicity to residues, depending on its valence and concentration, making it dangerous, and several industrial residues have this metal in their composition. The stabilization by solidification (S/S) is a treatment technology that uses residues containing metals in Portland cement matrix and it is necessary to evaluate the technical and environmental feasibility of the application. There are several studies on the feasibility of S/S for Cr waste, but few have specifically analyzed the Portland cement hydration process. This research aimed to evaluate the influence of water-insoluble Cr(III) compound (Cr2O3) and water-soluble Cr(VI) compound (K2CrO4) in the hydration products formation of Portland cement pastes in the initial ages, through the adding of 0%, 10%, 20% or 30% of these compounds separately. Analyzes of pH, X-ray diffraction (XRD), isothermal calorimetry, thermogravimetry (TG/DTG) and compressive strength were performed on the prepared samples. From the results, it was possible to verify that the incorporation of the water-insoluble Cr(III) compound (Cr2O3) delayed the hydration process of the Portland cement paste, but did not prevent the hydration compounds formation and got higher compressive strength than the reference sample. In addition, it was possible to evidence the formation of the compound called “bentorite”, whose chemical formula is Ca6Cr2(SO4)3(OH)12.26H2O. The incorporation of water-soluble Cr(VI) (K2CrO4) resulted in a more significant delay in the hydration process of the material and it was not possible to verify the formation of hydrated products according to the reference sample, besides the compressive strength was smaller. In these samples, it was also possible to evidence the formation of a hydrated product containing Cr, named hydrated calcium chromate (CaCrO4.H2O). The treatment of Cr(III) containing waste trough S/S could be a viable option with the application of other analysis such as environmental viability, while the S/S for Cr(VI) containing waste is not recommended.
Keywords: Cromo; Hidratação; Cimento; Óxido de cromo; Cromato de potássio; Chromium; Hydration; Cement; Potassium chromate.; Chromium oxide; ACCNPQ::Engenharias::Engenharia Civil